Differentiation of communicating hydrocephalus and presenile dementia by continuous recording of cerebrospinal fluid pressure. Issue 7 (July 1977) - Hartmann, A; Alberti, E
Abstract : Continuous monitoring of the cerebrospinal fluid pressure and observation of the pressure during intrathecal infusion of normal saline at two rates were performed in patients with communicating hydrocephalus and cerebral atrophy of other causes. Constant or temporarily increased cerebrospinal fluid pressure was observed only in communicating hydrocephalus. Reduction of intracranial pressure by a ventriculoatrial shunt was associated with clinical improvement. The intrathecal infusion test was capable of detecting reduced absorption of cerebrospinal fluid if more than one infusion rate was employed. Using both tests it is easier to determine which patients with communicating hydrocephalus should be treated with a shunt operation.